PENGARUH PEMBERIAN JERUK NIPIS HANGAT DAN MADU UNTUK MENGURANGI EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER 1 DI WILAYAH KERJA PUSKESMAS SUNGAI TUTUNG KERINCI - Arpen, Ratih Septiana; Marniati, Silvia (Ensiklopedia of Journal, 2025)
Abstract: Nausea and vomiting are common symptoms ranging from discomfort to prolonged vomiting, in medicine it is often known as morning sickness because it often appears in the morning. The aim of this research is to determine the effect of giving warm lime juice and honey to reduce emesis gravidarum in first trimester pregnant women in the Sungai Tutung Health Center working area, Kerinci Regency. The type of research used was Quasi Experimental Design in the form of One Group Pretest-Posttest with 15 respondents. The sampling technique used was non- probability with a purposive sampling method. The intervention was carried out by administering 30 ml of lime juice and 1 tablespoon of honey plus 250 ml of water. Before implementing the intervention, a first observation (pretest) was carried out. Then a second observation (posttest) was carried out after the intervention. Measuring the nausea and vomiting scale uses PUQE (pregnancy-unique quantification of emesis). And the results of the intervention before and after were tested using Paired Sample T- test. It was found that the average for emesis gravidarum before was 7.7 and after being given treatment it fell to 4.2. The skewness test results showed that the value before was 0.005 and after 1.479, it showed a result of ≤2 so that the data was normally distributed. There is an effect of giving warm lime juice on reducing emesis gravidarum in first trimester pregnant women in the Tutung River Health Center Working Area, from the results of statistical tests it was found that p value = 0.000 < 0.05. From this research, it is hoped that pregnant women can use hangta lime juice and honey to reduce emesis gravidarum.Keywords: Emesis Gravidarum, lime + honey, first trimester pregnant women,